PENGARUH DIVERSIFIKASI PRODUK ELEKTRONIK DAN REPUTASI PERUSAHAAN TERHADAP MINAT BELI ULANG PELANGGAN PADA UD.MEKAR SARI DI PRAYA LOMBOK TENGAH - Baiq Febrina dwi muliati; hermanto hermanto; edy herman mulyono (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This thesis is aimed at analyzing the effect of diversification of electronic products and the reputation of company on the repurchase interest in UD. Mekar Sari in Praya Central Lombok. This research is to analyse the effect of variable of company reputation on the repurchase interest in UD. Mekar Sari. This research is an associative study with all consumers buyimg the electronic products as the research population. The sample were 100 respondents. The data were analysed using SPSS.The research showed that Diversification of Electronic Products conducted by UD. Mekar Sari providing the various types, brands, and size of products has positive and significant effect on the repurchase interest of consuumers. The Company reputation was measured with the company’s competence, excellee, trust of cconsumers, the company’s experience had positive and significant effect on the repurchase interest in UD. Mekkar Sari.Keywords: Product Diversification, Company Reputation, Repurchase Interest